2018
DOI: 10.1371/journal.pone.0194813
|View full text |Cite
|
Sign up to set email alerts
|

High health literacy is associated with less obesity and lower Framingham risk score: Sub-study of the VGH-HEALTHCARE trial

Abstract: BackgroundsLower health literacy (HL) is associated with several cardiovascular disease (CVD) risk factors such as diabetes, hypertension, and metabolic syndrome (MS). The aim of our study was to investigate the association between HL and the Framingham 10-year risk score of CVD.MethodsFrom 2015–2016, 1010 subjects aged 23 to 88 years receiving health check-up in Taipei Veterans General Hospital had complete clinical evaluations and laboratory examinations. Fatty liver was diagnosed by ultrasonography. The sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 46 publications
(63 reference statements)
3
43
4
1
Order By: Relevance
“…Decreased health literacy is associated with similar health outcomes as diet-related chronic disease, such as higher hospitalization rates, poorer overall health status, and higher mortality rates [ 9 ]. Health literacy has also been associated with obesity [ 10 ], poorer dietary intake [ 11 ], and reduced physical activity [ 12 ], and it may have a mediating role in the relationship between chronic conditions and health outcomes through health behaviors. Health literacy is context-dependent [ 13 ], with individual levels increasing or decreasing according to life changes such as the onset of illness or entering a new life phase [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased health literacy is associated with similar health outcomes as diet-related chronic disease, such as higher hospitalization rates, poorer overall health status, and higher mortality rates [ 9 ]. Health literacy has also been associated with obesity [ 10 ], poorer dietary intake [ 11 ], and reduced physical activity [ 12 ], and it may have a mediating role in the relationship between chronic conditions and health outcomes through health behaviors. Health literacy is context-dependent [ 13 ], with individual levels increasing or decreasing according to life changes such as the onset of illness or entering a new life phase [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors also found that poor functional health literacy was associated with the presence of multiple comorbid conditions, such as hypertension, diabetes mellitus, and hyperlipidemia, consistent with multiple reports on the association between health literacy and these conditions. 15,30,31 Interestingly, 87% of Hispanic participants in the study had a diagnosis of hypertension, showing the significant relationship between health literacy and chronic conditions; high prevalence of hypertension is associated with lower health literacy. 29,31…”
Section: Discussionmentioning
confidence: 83%
“…15,30,31 Interestingly, 87% of Hispanic participants in the study had a diagnosis of hypertension, showing the significant relationship between health literacy and chronic conditions; high prevalence of hypertension is associated with lower health literacy. 29,31…”
Section: Discussionmentioning
confidence: 83%
“…Evidence of significant and inverse associations between health literacy and fasting plasma glucose is provided by another recent paper reporting on the associations of HL with an array of laboratory parameters among individuals aged 23-88 years receiving health checkup in Taipei, Taiwan (25).…”
Section: Discussionmentioning
confidence: 99%